2006
DOI: 10.1111/j.1365-2621.2006.tb08927.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution Enhancement and Post‐enhancement Storage Effects on the Quality, Sensory, and Retail Display Characteristics of Beef Triceps Brachii Muscles

Abstract: Beef triceps brachii muscles (6 d postmortem; n= 15; muscle sections n= 45) were sectioned into 3rds and allocated to 1 of 3 treatments. The treatments were untreated (CNT), or injected at a 12% pump rate with either tap water‐only (H2O) or a solution comprising tetrasodium pyrophosphate and sodium chloride (TSPP/ NaCl) at 0.4% and 1.0% target final product weight concentrations, respectively. Each muscle (comprising all 3 treatments) was then allocated to 2, 14, or 28 d of vacuum‐packaged 1°C storage. Purge l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…However, the day by treatment interaction was not significant ( P = 0.62). Baublits and others (2006b) reported a purge of 10.54% in beef triceps brachii injected with tap water at 12% pump rate, thus it can be stated that both treatments decreased the percent purge from enhanced beef strip loin steaks. Our observations support the theory that purge loss is related to final meat pH.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the day by treatment interaction was not significant ( P = 0.62). Baublits and others (2006b) reported a purge of 10.54% in beef triceps brachii injected with tap water at 12% pump rate, thus it can be stated that both treatments decreased the percent purge from enhanced beef strip loin steaks. Our observations support the theory that purge loss is related to final meat pH.…”
Section: Resultsmentioning
confidence: 97%
“…Similar results were also reported by Robbins and others (2002) who concluded that phosphate enhancement decreased cook loss and held > 6% of the injected solution. Baublits and others (2006b) reported 38.95% cook loss in beef triceps brachii muscles injected with only tap water. Based on their results, it can be concluded that both treatments in this study were effective in reducing cook loss.…”
Section: Resultsmentioning
confidence: 99%
“…Any level of treatment was beneficial, with the greatest shear force benefit occurring in muscle pumped to 30%. salt/phosphate solution has shown to increase waterbinding capacity and tenderness (Vote et al, 2000;Lawrence et al, 2004;Baublits et al, 2006). The chloride ions of salt are thought to bind to the myofilaments and increase the electrostatic repulsive force between them (Offer and Trinick, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement (averaged over aging time) increased the tenderness of the infraspinatus (chuck; from 8.7 to 10.3) the most, and that of the gluteus medius (round), and rectus femoris (round) the least (Table 5). Baublits and others (2006) reported that enhancement increased tenderness and juiciness, and slightly decreased the beef flavor of triceps brachii. In the present study, enhancement decreased the liver off‐flavor in the gluteus medius (round), and the psoas major (loin) but not in the other muscles.…”
Section: Effects Of Agingmentioning
confidence: 99%
“…It decreased purge loss of gluteus medius (round), rectus femoris (round), and psoas major (loin) by 3.2%, 2.33%, and 3.48%, respectively (Table 5). Baublits and others (2006) reported that enhancing triceps brachii with solutions containing phosphate and salt significantly decreased purge compared to its nonenhanced counterpart. They suggest that this may have been partially a pH effect as the phosphate/salt‐containing muscle pH was 5.9 while the control was 5.7.…”
Section: Effects Of Agingmentioning
confidence: 99%